Democracy promotion as US foreign policy Bill Clinton and democratic enlargement - Bouchet, Nicolas (London ; New York : Routledge, 2015)
'The role of democracy promotion in US foreign policy has increased considerably in the last three decades, booming especially in the immediate years after the end of the Cold War. The rise of democracy promotion originated in a long historical tradition that saw exporting American political values as instrumental in securing US security and economic interests, an idea which was expressed freely once Cold War strategic constraints disappeared. Under Bill Clinton, there was an explicit attempt to do so by reframing American strategy in terms of'democratic enlargement' and this book assesses the strategic use of democracy promotion in US foreign policy and its different outcomes during his presidency. Offering a comprehensive, global review of American democracy engagement with different regions of the world and key countries during a whole presidency, this book assesses how far the US has benefited from democracy promotion. It evaluates the instrumental value of democracy promotion for America by seeing whether the Clinton administration's efforts in this field, and their varying impacts to democratization abroad, were matched by progress in securing US strategic goals defined under enlargement, in particular reducing international conflicts and spreading economic liberalization around the world. The book explores how democracy became central to US post-Cold War strategy, how the Clinton administration developed the concept of democratic enlargement and tried to implement it, and why it remained influential on foreign policy throughout Clinton's presidency'--
1. The roots and influence of democratic enlargement -- 2. Institutionalizing democracy promotion -- 3. Operationalizing democracy promotion -- 4. Democratic enlargement in Eurasia and Eastern Europe -- 5. Democratic enlargement in the rest of the world -- 6. The rewards of democratic enlargement.
Includes bibliographical references and index.
Also available in print format.
Mode of access: World Wide Web.
Keywords: Clinton, Bill, -- 1946-; Democratization -- Government policy -- United States; United States -- Foreign relations -- 1993-2001.; Electronic books